Analisis Luasan Hutan Kota Berdasarkan Kemampuan Menyerap CO2, Kebutuhan O2 dan Kebutuhan Air di Kota Pekanbaru - Sriwanita, Capra; Mubarak, Mubarak; Nurhidayah, Tengku (Universitas Riau, 2017)
This research was conducted from July 2016 through October 2016 on the Urban Forests of Pekanbaru, Riau, Indonesia. The goals of this research are to analyze the area of urban forests required based on its ability and capacity for CO2 absorption and the need and capacity to provide O2 and water for its inhabitants in the city of Pekanbaru. The results of this research conclude that Urban Forest area required by the 2016 all area of the city of Pekanbaru based on the Urban Forest’s ability to absorb CO2 is 3,246 Ha, the Urban Forest area needed for O2 is 3,376 Ha and Urban Forest area needed for water is 7,360 Ha. The best approach in calculating the need for Urban Forests is based on water need.